2023
DOI: 10.1161/strokeaha.122.039797
|View full text |Cite
|
Sign up to set email alerts
|

24-Hour Carotid Stent Patency and Outcomes After Endovascular Therapy: A Multicenter Study

Abstract: Background: Management of extracranial internal carotid artery steno-occlusive lesion during endovascular therapy remains debated. Stent occlusion within 24 hours of endovascular therapy is a frequent event after acute carotid artery stenting, and we currently lack large population results. We investigated the incidence, predictors, and clinical impact of stent occlusion after acute carotid artery stenting in current clinical practice. Methods: Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In their study, delayed stent thrombosis was an independent predictor of unfavorable clinical outcome (odds ratio, 19.8 [95% CI, 2.8-296.8]). 9 However, patients who had unsuccessful reperfusion or stents that occluded during procedure would be more likely to be placed on aspirin alone rather than dual antiplatelet therapy and those with large ischemic strokes may have been more likely to be placed on aspirin alone due to increased hemorrhagic risk as suggested by Allard et al 6 Other than procedural medication, technical factors are important to consider to maintain carotid stent patency acutely. In elective or subacute settings of CAS, post-stent balloon angioplasty for residual post-stent carotid artery stenosis has been associated with microemboli, which was associated with neurological deficit after CAS.…”
Section: See Related Article P 124mentioning
confidence: 99%
See 4 more Smart Citations
“…In their study, delayed stent thrombosis was an independent predictor of unfavorable clinical outcome (odds ratio, 19.8 [95% CI, 2.8-296.8]). 9 However, patients who had unsuccessful reperfusion or stents that occluded during procedure would be more likely to be placed on aspirin alone rather than dual antiplatelet therapy and those with large ischemic strokes may have been more likely to be placed on aspirin alone due to increased hemorrhagic risk as suggested by Allard et al 6 Other than procedural medication, technical factors are important to consider to maintain carotid stent patency acutely. In elective or subacute settings of CAS, post-stent balloon angioplasty for residual post-stent carotid artery stenosis has been associated with microemboli, which was associated with neurological deficit after CAS.…”
Section: See Related Article P 124mentioning
confidence: 99%
“…The carotid occlusive/severe stenosis disease was due to atheroma (72%) and dissection (28%). 6 Allard and colleagues found that the rate of stent patency was related to reperfusion status, use of P2Y 12 inhibitors, and balloon angioplasty after CAS, whereas factors related to stent occlusion were use of multiple stents, dual layer stent, and dissection as the cause of occlusive disease. In fact, several factors-multiple stents, type of stent, reperfusion status and use of P2Y 12 inhibitors are related to carotid dissection where the occlusive lesion is longer and aggressive means are often needed to open the artery and maintain patency.…”
Section: See Related Article P 124mentioning
confidence: 99%
See 3 more Smart Citations